Synthesis Of PET/MWCNTs Electrospun Nanofiber With Polyester Fiber Support For Methylene Blue Removal - Steven Ling, Guang Hu (Universiti Sains Malaysia, 2021)
Occurrence of water pollution including contamination of dyes and heavy metals causes the quality of water to decrease significantly. One of the major dyes found in the wastewater is methylene blue (MB). The purposes of this study were to synthesis polyethylene terephthalate/multi-walled carbon nanotubes (PET/MWCNTs) electrospun nanofiber with polyester fibers(PES) as support and to investigate its adsorption performance on MB. The method to synthesis PET/MWCNTs electrospun nanofiber was using electrospinning process method. There are three major parameters such as contact time, adsorbent dosage and initial dye concentration were to be evaluated through batch mode experiment. The optimum contact time obtained for adsorption was 1440 minutes. PES+PET/MWCNTs had adsorption capacity of 0.3398 mg/g and removal efficiency of 13.63% which had better performance as compared to PES having adsorption capacity of 0.2529 mg/g and removal efficiency of 11.62%. The adsorption capacity showed a decreasing trend and the MB removal percentage showed an increasing trend when the adsorbent dosage increased. However, there was an increment in adsorption capacity and a reducing trend in MB removal percentage when the initial dye concentration increased. For adsorption isotherm, it was found that Langmuir isotherm model is relevant with the experimental data as compared to Freundlich and Temkin isotherm model. Pseudo-second-order kinetic model was more favourable in providing the details of the kinetic studies in MB adsorption. Thus, PET/MWCNTs electrospun nanofiber can be a potential adsorbent in removing MB dye from wastewater.